Formation of Mental Health and Character: Through the Habit of Reading Ratib Syaichona Cholil for Students of Islamic Higher Education - Mutmainah Mutmainah (Global Journal of Islamic Education, 2026)
Character building is very important for students as agents of change in the millennial era, where the younger generation has experienced a decline in morals due to the impact of globalization. Islamic religious institutes as Islamic educational institutions have an important role in character building because this is in line with Islamic Higher Education vision of becoming an Islamic religious university based on pesantren values that is integrity, competitive, and globally minded. The main issue in this study is how the habit of reading Rotib Syaichona Muhammad Cholil can contribute to character building among students. The objectives of this study are, first, to determine character building among students through reading Ratib Syaichona Cholil. The research method used is qualitative research with a phenomenological approach. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis includes data reduction, data display, and conclusions. Data validity is checked using triangulation. The results of the study show that the regular and consistent recitation of Ratib Syaichona Cholil by students can be a means of improving mental health: strengthening faith, bringing peace and tranquillity to the heart, and enhancing emotional and spiritual intelligence. It also improves character, including: religious character, family, friendship (communicative), discipline, and responsibility.